Graphitization of Glassy Carbon after Compression at Room Temperature - Shiell, T.; McCulloch, D.; McKenzie, D.; Field, M.; Haberl, B.; Boehler, R.; Cook, B.; Tomas Andres, Carla de; Suarez-Martinez, Irene; Marks, Nigel; Bradby, J. (The American Physical Society, 2018)
© 2018 American Physical Society. Glassy carbon is a technologically important material with isotropic properties that is nongraphitizing up to ~3000 °C and displays complete or "superelastic" recovery from large compression. The pressure limit of these properties is not yet known. Here we use experiments and modeling to show permanent densification, and preferred orientation occurs in glassy carbon loaded to 45 GPa and above, where 45 GPa represents the limit to the superelastic and nongraphitizing properties of the material. The changes are explained by a transformation from its sp2 rich starting structure to a sp3 rich phase that reverts to fully sp2 bonded oriented graphite during pressure release.